Dand5 is involved in zebrafish tailbud cell movement - Bota, Catarina; Martins, Gabriel G.; Lopes, Susana S. (Frontiers in Cell and Developmental Biology, 2023)
During vertebrate development, symmetry breaking occurs in the left-right organizer (LRO). The transfer of asymmetric molecular information to the lateral plate mesoderm is essential for the precise patterning of asymmetric internal organs, such as the heart. However, at the same developmental time, it is crucial to maintain symmetry at the somite level for correct musculature and vertebrae specification. Here, we demonstrate how left-right signals affect the behavior of zebrafish somite cell precursors. We describe a population of cells in the vicinity of the LRO, named Non-KV Sox17:GFP+ Tailbud Cells (NKSTCs), which migrate anteriorly and contribute to future somites. We show that NKSTCs originate in a cluster of cells aligned with the midline, posterior to the LRO, and leave that cluster in a left-right alternating manner, primarily from the left side. Fate mapping revealed that more NKSTCs integrated somites on the left side of the embryo. We then abolished the asymmetric cues from the LRO using dand5-/- mutant embryos and verified that NKSTCs no longer displayed asymmetric patterns. Cell exit from the posterior cluster became bilaterally synchronous in dand5-/- mutants. Our study revealed a new link between somite specification and Dand5 function. The gene dand5 is well known as the first asymmetric gene involved in vertebrate LR development. This study revealed a new link for Dand5 as a player in cell exit from the maturation zone into the presomitic mesoderm, affecting the expression patterns of myogenic factors and tail size.